Synthesis of highly efficient azure-to-blue-emitting Zn–Cu–Ga–S quantum dots. Issue 29 (28th March 2017) - Kim, Bu-Yong; Kim, Jong-Hoon; Lee, Ki-Heon; Jang, Eun-Pyo; Han, Chang-Yeol; Jo, Jung-Ho; Jang, Ho Seong; Yang, Heesun
Abstract : Non-Cd, azure-to-blue-emitting Zn–Cu–Ga–S/ZnS quantum dots with exceptional quantum yields of 78–83% are synthesized. Abstract : To realize blue emission-capable non-Cd I–III–VI quantum dots (QDs), we explore the synthesis of ternary Cu–Ga–S (CGS) QDs and subsequent quaternary Zn–Cu–Ga–S (ZCGS) via Zn alloying into a CGS host. The resulting ZCGS/ZnS core/shell QDs possess not only Zn content-dependent tunable emissions in the azure-to-blue range but also exceptional quantum yields of 78–83%.